Intervention study to improve the implementation of specific legislation related to food safety by Public Health Inspectors - Arnold, S.M (My University, 2005)
Study was carried out with the objective of evaluating the effectiveness of providing inservice training to PH Il, through the distance education method to improve the implementation of specific legislation on food safety. A high level of self-assessed competency was present in a majority of PHIl, in relation to performing tasks in implementing food legislation. However, observations of performance indicated that performance was poor in the activities carried out in the field as well as in the office. Three distance education modules on the subjects; legislation on food safety. legal procedures in food safety. food sampling and inspection and categorization of food handling establishments were administered during the intervention. Post intervention results showed that the knowledge had improved significantly in the intervention group in all subject areas, with 'food sampling' showing the highest improvement. Overall performance in all three activities i.e. inspection and categorization of food establishments, food sampling, and documentation and record' keeping showed a significant improvement in the intervention group. However, in comparison to the improvements seen in the performance of other two activities performance of certain activities in documentation and recordkeeping’ showed only a marginal improvement. The Present intervention was effective in improving the knowledge and performance of the PHIl in implementing legislation on food safety indicating the effectiveness of providing continuing education to PHIl using the distance education modules. As this method proved to be feasible, of low cost and has the ability to provide training without mobilizing the staff, it can be incorporated into !he existing training system for health care workers serving in the Department of Health Services